2012
DOI: 10.3109/00365548.2012.749422
|View full text |Cite
|
Sign up to set email alerts
|

Solitary cavitary pulmonary nodule may be a common CT finding in AIDS-associated pulmonary cryptococcosis

Abstract: Solitary cavitary pulmonary nodule may be a common CT finding in AIDS-associated PC. All AIDS patients with solitary cavitary pulmonary nodules on chest CT should be screened for Cryptococcus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Based on the available patients' data, at least 76.8% (43/56) of the nodular lesions could be demonstrated a relationship with PC. Those findings were closely consistent with our previous observation which suggested that solitary cavitary pulmonary nodule may be a common CT finding in HIV-associated PC[8]. Nevertheless, pulmonary nodular lesions with or without cavitation, although reported in other studies, were not recognized as common manifestations of HIV-associated PC [6, 7, 10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the available patients' data, at least 76.8% (43/56) of the nodular lesions could be demonstrated a relationship with PC. Those findings were closely consistent with our previous observation which suggested that solitary cavitary pulmonary nodule may be a common CT finding in HIV-associated PC[8]. Nevertheless, pulmonary nodular lesions with or without cavitation, although reported in other studies, were not recognized as common manifestations of HIV-associated PC [6, 7, 10].…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, we evaluated 11 HIV-infected patients with pulmonary abnormalities on chest CT scan and confirmed cryptococcal diseases outside of the lung. Interestingly, 9 patients had solitary pulmonary nodules that could be clinically related to cryptococcal infection [8]. This finding is inconsistent with the dominant perception of HIV-associated PC and necessitates further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Four cases of CM with good prognosis were early diagnosed before the onset of any neurologic symptoms. The patients were screened for cryptococcus infection because of the presence of pulmonary cavitary nodules, which were regarded as common lesions of HIVassociated pulmonary cryptococcosis (16). As mannitol was not used, these four patients were excluded from analysis.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This presents a dilemma for physicians and illuminates the importance of pertinent history, including exposures, in narrowing down the differential. In cases with nonnecrotizing granulomatous inflammation, noninfectious etiologies were more frequent . In addition, the incidence of the disease in the general population is poorly described and is primarily in the immunocompromised population .…”
Section: Introductionmentioning
confidence: 99%
“…In cases with nonnecrotizing granulomatous inflammation, noninfectious etiologies were more frequent. 1,2 In addition, the incidence of the disease in the general population is poorly described and is primarily in the immunocompromised population. 1 Of the infectious etiologies, pulmonary Cryptococcus is the most common cause of pulmonary infections in AIDS patients, which is rarely reported in pediatric oncology literature.…”
Section: Introductionmentioning
confidence: 99%